STUDI KRITIS BUKU AJAR PENDIDIKAN AGAMA ISLAM (PAI) TINGKAT MADRASAH ALIYAH TERBITAN KEMENTERIAN AGAMA TAHUN 2020 - Rosidin, Rosidin; Mardhatillah, Masyithah; Andriani, Fenty; Addakhil, Abdul Rahman (Jurnal Lektur Keagamaan, 2024)
Previous studies have identified radical content in Islamic religious education (PAI) textbooks. However, no comprehensive examination of 12 PAI textbooks in Indonesian Islamic high schools (Madrasah Aliyah) has been conducted. This study aims to address two questions: (1) What forms of non-moderate interpretation threaten religious moderation? (2) What forms of moderate interpretation strengthen religious moderation? This qualitative study gathered data through documentation, interviews with PAI textbook authors, and discussions with PAI experts in scientific forums. Data were analyzed using an interactive model. The findings of this study identified three forms of non-moderate interpretations in PAI textbooks that threaten religious moderation: (1) Textual interpretations undermining national commitment (wataniyyah), obedience to legislation (dusturiyyah), and acceptance of tradition (urfiyyah); (2) Partial interprettations compromising equality (mubadalah), compassion (rahamutiyyah), and justice (adalah); (3) Monodimensional interpretations on benefit (maslahat), humanity (insaniyyah), and tolerance (tasamuh). Conversely, moderate interpretations that strengthen religious moderation include: (1) Contextual interpretations combining objective text meanings with relevant subjective contexts; (2) Holistic interpretations integrating comprehensive understanding of the Qur'an through the maudu’i (thematic) method with collective expert validation (taqrir jama’i); (3) Multidimensional interpretations merging insights from Islamic science experts (shar’i) with those from natural, social, and humanities sciences (kawni). The practical implications highlight the need for developing mufassir education programs to produce contextual interpretations, expanding scientific forums for holistic interpretations, and enhancing collaboration between shar’i and kawni experts for multidimensional interpretations